Silicon Based GeSn p-i-n Photodetector for SWIR Detection - Hui Cong; Chunlai Xue; Jun Zheng; Fan Yang; Kai Yu; Zhi Liu; Xu Zhang; Buwen Cheng; Qiming Wang (IEEE Photonics Journal, 2016)
We reported an investigation of GeSn-based p-i-n photodetectors (PDs) with a ${\rm{Ge}}_{{\rm{0.92}}}{\rm{Sn}}_{{\rm{0.08}}}$ active layer grown on n-type Si (100) substrate using molecular beam epitaxy (MBE). The GeSn photodetector achieved a wide spectrum detection whose cutoff wavelength can reach to 2.3 μm. The PDs exhibited a high performance near 2.0 μm with a responsivity of 93 mA/W and a dark current of 171 μA under a reverse bias of 1 V at room temperature. This work represented a promising technology to develop Si-based short-wave infrared (SWIR) photodetectors.